Liquid-phase coated graphite negative electrode material, preparation method thereof and lithium ion battery

Through the liquid phase coating method, a dense carbon cladding layer is formed on the surface of the graphite negative electrode material, which solves the problems of difficulty in implanting lithium delivery and high deactivation rate during charging and discharging of traditional graphite negative electrode materials, and achieves high energy density and fast charging and discharging and excellent cycle performance.

CN119480968APending Publication Date: 2025-02-18合肥国轩新材料科技有限公司
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411588627.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-08
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

Traditional graphite negative electrode materials have difficulty in implanting lithium deliquency during charging and discharging, and have high inactivation rate, resulting in low reversible capacity and poor rate performance, making it difficult to meet the requirements of high energy density and high power density batteries.

Method used

The liquid phase coating method is used to fully mix the asphalt solution with artificial graphite, and a dense carbon coating layer is formed by heating and vacuuming and carbonization, thereby improving the structural stability of the graphite negative electrode material.

Benefits of technology

The high energy density, fast charging and discharging capability and excellent cycling performance of graphite negative electrode materials are achieved, and the rate performance and structural stability of the material are significantly improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119480968A_ABST
    Figure CN119480968A_ABST
Patent Text Reader

Abstract

The invention discloses a liquid-phase coated graphite negative electrode material, a preparation method thereof and a lithium ion battery, and the preparation method of the liquid-phase coated graphite negative electrode material comprises the following steps: adding asphalt into an organic solvent, and fully mixing to obtain an asphalt solution; and adding artificial graphite into the asphalt solution, fully mixing, heating, vacuumizing to remove the organic solvent, and carbonizing to obtain the liquid-phase coated graphite negative electrode material. According to the liquid-phase coated graphite negative electrode material, the preparation method thereof and the lithium ion battery provided by the invention, the fast-charging type graphite negative electrode material is prepared by a liquid-phase coating method, high capacity and excellent cycle performance are considered at the same time, and the liquid-phase coated graphite negative electrode material has remarkable practical value in the aspects of increasing high-energy density and high-rate charge and discharge requirements.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of lithium ion batteries, and in particular relates to a liquid-phase coated graphite negative electrode material and a preparation method thereof, and a lithium ion battery. Background Art

[0002] Lithium-ion batteries have the advantages of high specific capacity, no charge and discharge memory effect, green environmental protection, and no pollution. They are not only widely used in portable electronic products, but also in aerospace, military, electric vehicles, energy storage and other fields. Artificial graphite materials have the advantages of high specific capacity, good cycle performance, low lithium insertion and extraction platform, and low cost, making them the most commercially valuable negative electrode materials for power lithium-ion batteries.

[0003] The main structure of a traditional lithium-ion battery includes: positive electrode, negative electrode, separator, and electrolyte. Among the factors that affect the performance of lithium-ion batteries, in addition to the positive electrode material, it is the negative electrode material. Whether a negative electrode material with high performance and fast charging and discharging can be prepared directly determines the performance of the battery. In general, high-performance negative electrode materials should have the characteristics of small free energy change in highly reversible embedding reactions during charging and discharging, high free diffusion coefficient of lithium ions in negative electrode materials, high electrical conductivity, and stable thermodynamic properties. At present, the research work on negative electrode materials is mainly focused on various carbon materials and other compounds with special structural characteristics. The most used negative electrode material is carbon-based material, mainly graphite, which has the advantages of low price, wide range of raw materials, good processing performance, good conductivity, stable charging and discharging voltage platform and low cost, and has universal applicability to various lithium-ion batteries. However, its disadvantages are also prominent. Lithium ions are difficult to deintercalate in graphite and have a high deactivation rate, resulting in problems such as low reversible capacity and poor rate performance. Moreover, the capacity density and conductivity of graphite materials themselves are not particularly outstanding among various types of materials. As a result, energy density, high current rate performance and cycle stability are severely limited, making it difficult to meet the growing requirements for high energy and high power density batteries.

[0004] Therefore, providing a high-performance negative electrode material with excellent rate performance and cycle performance while taking into account high capacity has become an important issue in the development of lithium batteries. Summary of the invention

[0005] In order to solve the technical problems existing in the background technology, the present application discloses a liquid-phase coated graphite negative electrode material, a preparation method thereof and a lithium-ion battery. A fast-charging graphite negative electrode material is prepared by the liquid-phase coating method, which has both high capacity and excellent cycle performance, and has significant practical value in terms of the growing needs for high energy density and large-rate charging and discharging.

[0006] The present invention provides a method for preparing a liquid-phase coated graphite negative electrode material, comprising the following steps:

[0007] S1, adding asphalt into an organic solvent and mixing thoroughly to obtain an asphalt solution;

[0008] S2. Add artificial graphite to the asphalt solution and mix thoroughly, heat and evacuate to remove the organic solvent, and then carbonize to obtain the liquid-coated graphite negative electrode material.

[0009] In the present invention, asphalt is fully dissolved in an organic solvent, and the obtained solution is then used to coat artificial graphite. The low-viscosity asphalt solution obtained in this way can not only be effectively coated on the surface of artificial graphite, but also is conducive to deposition on the surface of artificial graphite to form a dense coating structure. After that, the organic solvent is removed and carbonized, while eliminating excess volatiles, the residual asphalt is melted and impregnated into the gaps in the artificial graphite, achieving a denser coating, which greatly improves the stability of the graphite negative electrode material structure, and finally obtains a graphite negative electrode material with excellent rate performance, high capacity and high cycle performance.

[0010] Preferably, in step S1, the asphalt is coal asphalt and / or petroleum asphalt; the organic solvent is at least one of tetrahydrofuran, toluene, chloroform, carbon disulfide or N-methylpyrrolidone;

[0011] Preferably, the mass ratio of the asphalt to the organic solvent is 1:5-10.

[0012] Preferably, in step S2, the artificial graphite is obtained by coarsely crushing and grinding an artificial graphite precursor, and then performing pre-carbonization and graphitization treatment;

[0013] Preferably, the artificial graphite precursor is at least one of petroleum coke, asphalt coke or needle coke;

[0014] Preferably, the graphitization temperature is 2500-3000° C., and the time is 12-36 hours.

[0015] Preferably, in step S2, the weight ratio of the artificial graphite to asphalt is 100:10-20.

[0016] Preferably, in step S2, the heating and vacuuming temperature is 65-80°C, and the vacuum degree is -(0.5-2)MPa.

[0017] In the present invention, the heating and vacuuming temperature is 65-80°C. If it is too high, the evaporation will be too fast and the coating effect will be poor. If it is too low, the reaction time will be too long and the efficiency will be too low.

[0018] Preferably, in step S2, the carbonization treatment temperature is 800-1000°C and the time is 4-10h.

[0019] Preferably, before step S2, the method further comprises: subjecting the artificial graphite to surface oxidation treatment, and then subjecting it to a condensation reaction with allyl chloroformate, and then subjecting it to a graft copolymerization reaction with SBS;

[0020] Preferably, the surface oxidation treatment is achieved by using a hydrogen peroxide oxidation agent;

[0021] Preferably, the graft copolymerization reaction is carried out using benzoyl peroxide as an initiator.

[0022] Preferably, the weight ratio of the artificial graphite, allyl chloroformate and SBS is 1:0.005-0.01:0.01-0.05.

[0023] In the present invention, artificial graphite is subjected to surface oxidation treatment so that the surface and edge of the artificial graphite are oxidized and oxygen-containing functional groups are formed, which can undergo condensation reaction with allyl chloroformate so that the surface of the artificial graphite has acrylate groups, and then the artificial graphite is copolymerized with styrene-butadiene-styrene block copolymer (SBS) so that the surface of the artificial graphite is grafted with SBS. Since the surface of the artificial graphite is grafted with SBS, the adsorption effect on asphalt is increased, especially the affinity for light components in asphalt is stronger, so that a "polymer group" with artificial graphite as the core can be formed, and a more stable network structure is formed between the SBS grafted on the surface of the artificial graphite and the asphalt adsorbed on the surface of the artificial graphite. After carbonization, a more stable carbon shell can be formed on the surface of the artificial graphite, so as to obtain a graphite negative electrode material with higher electrochemical performance.

[0024] The present invention also provides a liquid-phase coated graphite negative electrode material, which is prepared by the above preparation method.

[0025] The present invention also provides a lithium ion battery, which comprises the above liquid-phase coated graphite negative electrode material.

[0026] Beneficial effects of the present invention:

[0027] The present invention provides a liquid-coated graphite negative electrode material, a preparation method and an application thereof, wherein artificial graphite is subjected to carbon coating modification treatment using an organic solvent solution of asphalt to obtain the negative electrode material; the graphite negative electrode material prepared by the present invention has both high energy density and fast charge and discharge capabilities, and has a relatively stable structure, and can meet repeated charge and discharge requirements.

[0028] Compared with traditional solid-phase carbon-coated graphite negative electrode materials, since the solid-phase coating has always had problems such as insufficient coating and easy falling off during the processing, resulting in instability and poor uniformity of the product, the present invention proposes a liquid-phase coated graphite negative electrode material, which uses asphalt as a coating agent and a high-solubility organic reagent as a solvent, which can effectively coat the graphite powder and prevent the graphite layer from dissociating or even peeling off. Therefore, its coating uniformity, integrity, and structural stability are greatly improved compared with the solid-phase carbon-coated graphite negative electrode material, and the cycle performance and rate performance of the graphite negative electrode material are effectively improved. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] Figure 1 This is the SEM image of the liquid-coated graphite negative electrode material described in Example 1. DETAILED DESCRIPTION

[0030] Example 1

[0031] This embodiment provides a method for preparing a liquid-phase coated graphite negative electrode material, which specifically includes:

[0032] (1) After crushing and grinding needle coke (volatile matter ≤ 10.0%), pre-carbonization treatment is performed at 600° C. to obtain carbonized powder with a D50 of 10.12 μm, and the carbonized powder is graphitized at 2800° C. for 24 hours to obtain artificial graphite;

[0033] (2) adding coal tar pitch (softening point: 150° C.) into tetrahydrofuran, stirring thoroughly until completely dissolved, to obtain a 15 wt% tar pitch solution;

[0034] (3) The artificial graphite and the asphalt solution were added to a VC mixer at a mass ratio of 1:1 and mixed thoroughly for 2 hours. The mixture was heated to 70°C and then evacuated to -1.0 MPa. The mixture was kept warm until all the tetrahydrofuran was removed. The mixture was post-carbonized at 900°C in a nitrogen atmosphere for 7 hours to obtain the liquid-coated graphite negative electrode material.

[0035] Example 2

[0036] This embodiment provides a method for preparing a liquid-phase coated graphite negative electrode material, which specifically includes:

[0037] (1) After crushing and grinding needle coke (volatile matter ≤ 10.0%), pre-carbonization treatment is performed at 600° C. to obtain carbonized powder with a D50 of 10.12 μm, and the carbonized powder is graphitized at 2800° C. for 24 hours to obtain artificial graphite;

[0038] (2) adding coal tar pitch (softening point: 150° C.) into tetrahydrofuran, stirring thoroughly until completely dissolved, to obtain a 20 wt% tar pitch solution;

[0039] (3) The artificial graphite and the asphalt solution were added to a VC mixer at a mass ratio of 1:1 and mixed thoroughly for 2 hours. The mixture was heated to 65°C and then evacuated to -0.5 MPa. The mixture was kept warm until all the tetrahydrofuran was removed. The mixture was post-carbonized at 800°C in a nitrogen atmosphere for 10 hours to obtain the liquid-coated graphite negative electrode material.

[0040] Example 3

[0041] This embodiment provides a method for preparing a liquid-phase coated graphite negative electrode material, which specifically includes:

[0042] (1) After crushing and grinding needle coke (volatile matter ≤ 10.0%), pre-carbonization treatment is performed at 600° C. to obtain carbonized powder with a D50 of 10.12 μm, and the carbonized powder is graphitized at 2800° C. for 24 hours to obtain artificial graphite;

[0043] (2) adding coal tar pitch (softening point: 150° C.) into tetrahydrofuran, stirring thoroughly until completely dissolved, to obtain a 10 wt% tar pitch solution;

[0044] (3) The artificial graphite and the asphalt solution were added to a VC mixer at a mass ratio of 1:1 and mixed thoroughly for 2 hours. The mixture was heated to 80°C and then evacuated to -2.0 MPa. The mixture was kept warm until all the tetrahydrofuran was removed. The mixture was then post-carbonized at 1000°C for 4 hours in a nitrogen atmosphere to obtain the liquid-coated graphite negative electrode material.

[0045] Example 4

[0046] This embodiment provides a method for preparing a liquid-phase coated graphite negative electrode material, which specifically includes:

[0047] (1) After crushing and grinding needle coke (volatile matter ≤ 10.0%), pre-carbonization treatment is performed at 600° C. to obtain carbonized powder with a D50 of 10.12 μm, and the carbonized powder is graphitized at 2800° C. for 24 hours to obtain artificial graphite;

[0048] (2) The artificial graphite and water are mixed in a mass ratio of 1:10, and the mixture is heated to 80° C. and ultrasonically dispersed uniformly. Then, an acidic hydrogen peroxide solution (sulfuric acid content is 10wt%, hydrogen peroxide content is 20wt%) in an amount 10 times the mass of the artificial graphite is added, and the mixture is stirred for reaction for 4 hours, filtered, washed with water, and dried to obtain oxidized artificial graphite; the oxidized artificial graphite is added to toluene in an amount 3 times the mass of the artificial graphite and ultrasonically dispersed uniformly. Then, triethylamine in an amount 0.5wt% of the mass of the artificial graphite and allyl chloroformate in an amount 1wt% of the mass of the artificial graphite are added, and the mixture is stirred for reaction for 4 hours after heating to 80° C., and SBS (model: YH791) in an amount 2% of the mass of the artificial graphite and benzoyl peroxide in an amount 0.5% of the mass of the artificial graphite are added, and the mixture is stirred for reaction for 6 hours after heating to 80° C., and the mixture is cooled, and toluene is removed to obtain SBS grafted modified artificial graphite;

[0049] (3) adding coal tar pitch (softening point: 150° C.) into tetrahydrofuran, stirring thoroughly until completely dissolved, to obtain a 15 wt% tar pitch solution;

[0050] (3) The SBS grafted modified artificial graphite and the asphalt solution were added into a VC mixer at a mass ratio of 1:1 and mixed thoroughly for 2 hours. The mixture was heated to 70°C and then evacuated to -1.0 MPa. The mixture was kept warm until all the tetrahydrofuran was removed. The mixture was post-carbonized at 900°C in a nitrogen atmosphere for 7 hours to obtain the liquid-coated graphite negative electrode material.

[0051] Figure 1 This is the SEM image of the liquid-coated graphite negative electrode material described in Example 1, refer to Figure 1 It can be seen that the liquid phase coating method can form an effective and dense coating layer on the surface of artificial graphite, so that the surface of the coated graphite material is uniform and high in purity, thus forming a relatively stable structural framework, improving the overall dispersion ability, and meeting the requirements of Li + The rapid embedding and de-embedding of ions makes fast and high-rate charging and discharging possible.

[0052] Comparative Example 1

[0053] This comparative example proposes a method for preparing a graphite negative electrode material, which specifically includes:

[0054] (1) After crushing and grinding needle coke (volatile matter ≤ 10.0%), pre-carbonization treatment is performed at 600° C. to obtain carbonized powder with a D50 of 10.21 μm, and the carbonized powder is graphitized at 2800° C. for 30 hours to obtain artificial graphite;

[0055] (2) The artificial graphite and coal tar pitch (softening point of 150° C.) were added into a VC mixer at a mass ratio of 100:15 and mixed thoroughly for 2 h, and then post-carbonized at 900° C. for 7 h in a nitrogen atmosphere to obtain the graphite negative electrode material.

[0056] The graphite negative electrode material of the embodiment or comparative example is used as a negative electrode material for a lithium ion battery. Specifically, the graphite negative electrode material, polyvinylidene fluoride (PVDF) and conductive carbon black are mixed in a mass ratio of 93:5:2, placed in a high-speed disperser and stirred to prepare an active slurry, and coated on a copper foil to obtain a negative electrode sheet;

[0057] The above-mentioned negative electrode sheet was used as the negative electrode, the metal lithium sheet was used as the counter electrode, Celgard2325 was used as the separator, 1 mol / LLiPF6 (the solvent was a mixture of ethylene carbonate EC and diethyl carbonate DEC in a volume ratio of 1:1) was used as the electrolyte, and a CR2032 button battery shell was used to assemble a button battery in an argon-protected glove box.

[0058] The electrochemical performance of the button battery was tested using the Blue Electric Battery Test System of Wuhan Blue Electric Electronics Co., Ltd. The test voltage range was 0.005-2V and the charge and discharge rate was 0.1C.

[0059] Table 1 Electrochemical performance test results of the graphite negative electrode materials described in the examples and comparative examples

[0060]

[0061] It can be seen from Table 1 above that the liquid-phase coated graphite negative electrode material of the present invention can provide more lithium insertion sites and channels, significantly improve the material's fast-charge performance, and the first discharge specific capacity exceeds 354 mAh / g, while the first efficiency is greater than 93%, showing good powder characteristics and electrochemical properties.

[0062] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.

Claims

1. A method for preparing a liquid-phase coated graphite negative electrode material, characterized in that: The steps include: S1, adding asphalt into an organic solvent and mixing thoroughly to obtain an asphalt solution; S2. Add artificial graphite to the asphalt solution and mix thoroughly, heat and evacuate to remove the organic solvent, and then carbonize to obtain the liquid-coated graphite negative electrode material.

2. The method for preparing the liquid-phase coated graphite negative electrode material according to claim 1, characterized in that: In step S1, the asphalt is coal asphalt and / or petroleum asphalt; the organic solvent is at least one of tetrahydrofuran, toluene, chloroform, carbon disulfide or N-methylpyrrolidone; Preferably, the mass ratio of the asphalt to the organic solvent is 1:5-10.

3. The method for preparing the liquid-phase coated graphite negative electrode material according to claim 1 or 2, characterized in that: In step S2, the artificial graphite is obtained by crushing and grinding an artificial graphite precursor, and then performing pre-carbonization and graphitization treatment; Preferably, the artificial graphite precursor is at least one of petroleum coke, asphalt coke or needle coke; Preferably, the graphitization temperature is 2500-3000° C., and the time is 12-36 hours.

4. The method for preparing the liquid-phase coated graphite negative electrode material according to any one of claims 1 to 3, characterized in that: In step S2, the weight ratio of the artificial graphite to the asphalt is 100:10-20.

5. The method for preparing the liquid-phase coated graphite negative electrode material according to any one of claims 1 to 4, characterized in that: In step S2, the heating and vacuuming temperature is 65-80°C, and the vacuum degree is -(0.5-2)MPa.

6. The method for preparing the liquid-phase coated graphite negative electrode material according to any one of claims 1 to 5, characterized in that: In step S2, the carbonization treatment temperature is 800-1000°C and the time is 4-10h.

7. The method for preparing the liquid-phase coated graphite negative electrode material according to any one of claims 1 to 6, characterized in that: Before step S2, the method further includes: subjecting the artificial graphite to surface oxidation treatment, performing a condensation reaction with allyl chloroformate, and then performing a graft copolymerization reaction with SBS; Preferably, the surface oxidation treatment is achieved by using a hydrogen peroxide oxidation agent; Preferably, the graft copolymerization reaction is carried out using benzoyl peroxide as an initiator.

8. The method for preparing the liquid-phase coated graphite negative electrode material according to claim 7, characterized in that: The weight ratio of the artificial graphite, allyl chloroformate and SBS is 1:0.005-0.01:0.01-0.

05.

9. A liquid-coated graphite negative electrode material, characterized in that: The compound is prepared by the preparation method according to any one of claims 1 to 8.

10. A lithium ion battery, characterized in that: It includes the liquid-phase coated graphite negative electrode material as described in claim 9.